The Effect of Peer Assisted Learning Strategies (PALS) Toward Students' Reading Comprehension - Khotimah, Devi Nurul; Mulyana, Agus; Nuraini, Hery (Foremost Journal, 2022)
The study's purpose was to clarify how the peer-assisted learning method (PALS) affected students' reading comprehension in order to increase their engagement in text discussion and increase their motivation to read. The result showe that s Students' knowledge of daily life and the environment was increased. The 253 students in the entire 10th grade courses at SMAN 14 Kota Tangerang made up the study's sample population. Then, using random sampling, 72 students were chosen as the research's sample. Peer Assisted Learning Strategy (PALS) as a variable X and short answer test students' reading comprehension as a variable Y were used to collect the data. Pre- and post-test data were collected. While the control class scored 28.64 with a minimum of 7 and a maximum of 47, the experimental class's PALS score was 38.44, with a minimum of 10 and a maximum of 57. The results of the Mann-Whitney U Test's calculation of the null hypothesis can be seen; the value in the control class was lower than the t-table with a value of 0.0650.05, while the value in the experiment class was higher with a value of 0.109>0.05. Given that Ha was approved and Ho was refused, it can be said that the Peer Assisted Learning Strategy (PALS) has a considerable impact on students' reading comprehension in the 10th grade of SMAN 14 Kota Tangerang.